A systematic review of Gymnema sylvestre in obesity and diabetes management. (19th November 2013) - Pothuraju, Ramesh; Sharma, Raj Kumar; Chagalamarri, Jayasimha; Jangra, Surender; Kumar Kavadi, Praveen
Abstract The prevalence of obesity is associated with many health‐related problems. Currently, more than 300 million people are considered to be obese. According to the World Health Organization (WHO), by 2030, 87 and 439 million people will be affected in India and the world, respectively. Today, herbal medicines are gaining interest in the treatment of obesity and diabetes, because of their minimal side effects. Gymnemic acid – an active component isolated from Gymnema sylvestre – has anti‐obesity and antidiabetic properties, decreases body weight and also inhibits glucose absorption. Several components extracted from Gymnema prevent the accumulation of triglycerides in muscle and liver, and also decrease fatty acid accumulation in the circulation. In this paper, an attempt has been made to review the effects of various extracts from Gymnema sylvestre in the regulation of carbohydrate and lipid metabolism in both animal and clinical studies. © 2013 Society of Chemical Industry